Manifesto of the New Economy : Institutions and Business Models of the Digital Society. - Dolgin, Alexander. (Springer Berlin / Heidelberg, 2011)
This examination of the future of the 'digital society'--and its monetization--presents the business model for content producing industries and interrogates a host of issues from the economics of people's spare time to the meaning of the term 'club economics'.